Osseous Metaplasia in Rectal Polyp: A Case Report with Review of Probable Pathogenesis - Azar Naimi; Mehrdad Hosseinpour (Advanced Biomedical Research, 2018)
Heterotopic bone formation is a rare event in gastrointestinal lesions, especially in the pediatric population. Osseous metaplasia is exceedingly rare in colonic polyps. We present a case of rectal juvenile polyp with stromal osseous metaplasia in a 10-year-old male child. This histologic finding is very rare in children with colorectal polyps.